Components of School-Based Interventions Stimulating Students’ Intrapersonal and Interpersonal Domains: A Meta-analysis - Mertens, Esther (Clin Child Fam Psychol Rev, 2020)
Many universal school-based interventions aim to stimulate students’ intrapersonal (e.g., self-esteem) and interpersonal (e.g., school climate) domains. To improve our understanding of why some of these interventions yield stronger effects than others, we identified intervention components that are related to stronger or weaker intervention effects. We systematically searched four databases (i.e., PsycINFO, PubMed, ERIC, CENTRAL) for controlled evaluations of universal school-based interventions. In total, 104 included studies (529 included effect sizes) reported on 99 unique interventions. Interventions showed small positive effects on the intrapersonal (d = 0.19) and interpersonal (d = 0.15) domains. Focusing on self-awareness and problem solving, using more active learning approaches, and using more extensive interventions predicted stronger intervention effects on aspects of both domains. In contrast, efforts to improve emotion regulation, assertiveness, cognitive coping, and using group discussions predicted weaker intervention effects. Furthermore, commonly implemented components were not necessarily related to stronger intervention effects and components that were related to stronger effects were not necessarily often implemented. Our findings highlight the need to carefully select components for inclusion in interventions. PROSPERO Registration Number: CRD42019137981.